ANALISIS HAK ANGKET DEWAN PERWAKILAN RAKYAT DAERAH KOTA BANDAR LAMPUNG TERHADAP KEBIJAKAN WALIKOTA BANDAR LAMPUNG - AGUS ISKANDAR (KEADILAN PROGRESIF, 2018)
The Regional Government as the Regional Executive and the Regional House of Representatives as the Regional Legislative Party although both are different regional institutions but the DPRD has the same position with the Regional Head. To be able to carry out its function the DPRD as the regional legislature has the right of the budget Asking questions for each members, Request information, Make changes, Submit statements of opinion, Initiatives and Investigations. The research problem that will be discussed in the research is how the procedure of execution of the Right of Question by City Council of Bandar Lampung toward the policy of Mayor of Bandar Lampung. The normative and empirical juridical approach method, using secondary data and primary data, and qualitative juridical analysis. The results of the research note that the procedure of implementation of the right of inquiry in Bandar Lampung City area so far has not used the right of questionnaire because of the problems of Mayor of Bandar Lampung policy can still be solved by caramusyawarah. The Government should make a regulation on the use of more specific right of inquiry in order to avoid the misuse of the right of inquiry by legislative that its use is not taking sides to the people